2013
DOI: 10.5103/kjsb.2013.23.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Head Posture and Breathing Pattern on Muscle Activities of Sternocleidomastoid and Scalene during Inspiratory Respiration

Abstract: The purpose of this study was to determine the effect of head posture and respiratory pattern on muscle activities of sternocleidomastoid (SCM) and scalene during maximal respiration. The seventeen subjects with upper-costal breathing pattern were participated in this study. Surface electromyography was used to measure the muscles activities of SCM and scalene. The volume and velocity of inspiration were monitored by using the spirometer in each subject. Each subject was performed the 3-cycle of respiration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…in 2018. In this study, it was concluded that performing balloon blowing exercises in a 90/90 bridge position with a ball showed significant improvement in respiratory function [17]. The study was also similar to a 2011 study by Sam Cheol et al, which found that balloon blowing exercise was beneficial in boosting respiratory activity [25] The results of the study were also similar to those of Hun-lo Kim et [15].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…in 2018. In this study, it was concluded that performing balloon blowing exercises in a 90/90 bridge position with a ball showed significant improvement in respiratory function [17]. The study was also similar to a 2011 study by Sam Cheol et al, which found that balloon blowing exercise was beneficial in boosting respiratory activity [25] The results of the study were also similar to those of Hun-lo Kim et [15].…”
Section: Discussionsupporting
confidence: 84%
“…These exercises serve to increase core muscle activation while also strengthening the muscles [16]. The use of a ball in a 90/90 bridge position with a balloon blowing exercise was found to improve pulmonary function and lung capacity, increasing FVC and FEV1 [17].…”
Section: Introductionmentioning
confidence: 99%
“…This cannot be ignored because excessive SCM activation compensates for this weakness12 ) . Terret et al13 ) reported excessive SCM activation in their study, and Koh and Jung14 ) investigated %MVIC of SCM and scalene muscles in FHP and neutral position in their study. Both muscles showed higher muscle activities when subjects were in FHP than when they were in the neutral position.…”
Section: Discussionmentioning
confidence: 88%
“…The upper trapezius originates from the occipital bone and inserts at the clavicle, acromion, and scapular spine 10 ) . The scalenes originate from the second to seventh transverse process and the costal process of the cervical vertebra and insert at the first and second ribs 11 ) . The levator scapulae originate from the first to fourth transverse process of the cervical vertebra and insert at the scapular superior angle 12 ) .…”
Section: Discussionmentioning
confidence: 99%